A report on practice in industry training in fish preservation. - Francisco, Perpetua Socorro A. (College of Fisheries, University of the Philippines, 1976)
The U.P. College of fisheries requires prospective graduates to undergo four months training in different fishing establishments, either privately owned or Government-owned. Under the apprenticeship program, a student can apply the theories learned in the classroom and observe existing working conditions in the industry. This will provide the fisheries student the opportunity to broaden their experiences on the practical aspects of fishery development. Students are made to work or observed in different plants. Pertinent data, illustrations and pictures are compiled, evaluated and respective recommendations are made. A report on the practice-in-industry training in fish preservation is a modest attempt to record the various steps, facts and important observations gathered during the entire period of apprenticeship. The topics discussed here are smoking of fish (tinapa), fish sauce (patis) making, fish paste (bagoong) making, fishmeal manufacture and freezing and cold storage. This work strives to illustrate the fruit of four months field association in pictures and illustrations.